Lean Management in Pediatric Intensive Care Units (PICU) - D. Galante (Pediatric Anesthesia and Critical Care Journal (PACCJ))
Lean management, originally developed in the manufac- turing sector, has been increasingly applied in healthcare settings, particularly in intensive care units (ICUs). Its principles focus on improving efficiency, reducing waste, and enhancing patient outcomes by optimizing work- flows and resource utilization. In Pediatric Intensive Care Units (PICUs), where complex care and high patient acu- ity are common, the application of Lean principles has the potential to significantly improve both the quality of care and operational performance.